Vector competence of Aedes albopictus for yellow fever virus: risk of reemergence of urban yellow fever in Brazil - Caldeira, Rossela Damasceno (2023)
The risk of the emergence and reemergence of zoonoses is high in regions that are under the strong influence of anthropogenic actions, as they contribute to the risk of vector disease transmission. Yellow fever (YF) is among the main pathogenic arboviral diseases in the world, and the Culicidae Aedes albopictus has been proposed as having the potential to transmit the yellow fever virus (YFV). This mosquito inhabits both urban and wild environments, and under experimental conditions, it has been shown to be susceptible to infection by YFV. In this study, the vector competence of the mosquito Ae. albopictus for the YFV was investigated. Female Ae. albopictus were exposed to non-human primates (NHP) of the genus Callithrix infected with YFV via a needle inoculation. Subsequently, on the 14th and 21st days post-infection, the legs, heads, thorax/abdomen and saliva of the arthropods were collected and analyzed by viral isolation and molecular analysis techniques to verify the infection, dissemination and transmission. The presence of YFV was detected in the saliva samples through viral isolation and in the head, thorax/abdomen and legs both by viral isolation and by molecular detection. The susceptibility of Ae. albopictus to YFV confers a potential risk of reemergence of urban YF in Brazil.